Effect of Phenobarbital and Glutethimide on Biological Half-Life of Warfarin - Corn, M (Thrombosis and Haemostasis, 1966)
The administration of phenobarbital or glutethimide significantly decreased the half-life of warfarin in 21 of 34 hospitalized patients. Patients who demonstrated a decrease could not be distinguished from apparent non-responders by age, weight, sex, or race. These sedatives did not detectably affect gastrointestinal absorption of warfarin. The observed decrease in warfarin half-life supports the concept that barbiturates and other drugs can increase the concentration of some drug-metabolizing enzymes. Since anticoagulating activity of coumarins is related to drug half-life, it is suggested that barbiturates or glutethimide therapy be discontinued in patients who appear refractory to anticoagulation with coumarins.